Regulatory Restrictions Across U.S. Protein Supply Chains. (19th February 2022) - Staples, Aaron J.; Chambers, Dustin; Melstrom, Richard T.; Malone, Trey
Abstract: Food regulations protect consumer health, mitigate environmental concerns, and promote animal welfare, but they can also hinder innovation, limit entrepreneurship, and generate higher consumer prices. This study examines the number of federal and state regulatory restrictions affecting the beef, pork, poultry, sheep, goat, and seafood industries, including processing, wholesale distribution, and retail sales. We also examine state regulatory heterogeneity associated with animal protein products. Our results suggest that protein supply chains have become subject to tens of thousands of regulatory constraints over the past half-century. We also find substantial heterogeneity in the number of state restrictions associated with animal production, indicative of large differences in the amount of administrative law across states. Results highlight that the patchwork approach of U.S. food policy creates overlapping, cumbersome guidelines for manufacturers, and given the interconnectivity of modern food supply chains, the framework can create additional hurdles for interstate commerce.